Electromagnetic Performance of Segmented Stator Flux Switching Permanent Magnet Motor - Ahmad Syukri, Muhammad Aiman; Sulaiman, Erwan; Naufal, S. M. (Evolution in Electrical and Electronic Engineering, 2022)
This paper describes the electromagnetic performance of the segmental stator flux switching permanent magnet motor. Few designs of the electrical motor with segmental stator structure have been studied, such as flux switching motor (FSM) and flux switching permanent magnet (FSPM) motor to produce a design with unique characteristics. Those characteristics are to isolate each phase of winding or a group of winding to be more independent and without any medium interconnect between segments. The objective of this paper is to analyze the electromagnetic performance of segmental stator FSPM on the issue relating to the stator segmentation technique and compare the electromagnetic performance of conventional and segmental stator FSPM. The performance of the design using no load and load analyses is investigated by using 2-D finite element analysis (FEA) software develop by JMAG designer version 16.0. After summarizing and comparing the performance of all designs, the segmental FSPM motor has lower torque than the other two design models, which might accelerate the motor’s speed. In terms of electromagnetic performance, the conventional FSPM motor outperforms the segmental FSPM motor with high torque of 215.16 Nm value than other designs and has a low output power to rotate the motor. In conclusion, the result is satisfactory as it achieves the objectives of comparison of electrical performance between the designs.